14-3-3ε protein-immobilized PCL-HA electrospun scaffolds with enhanced osteogenicity - Rivero, G.; Aldana, A. A.; Frontini Lopez, Y. R.; Liverani, Liliana; Boccaccini, Aldo R.; Bustos, D. M.; Abraham, G. A. (Journal of Materials Science: Materials in Medicine, 2019)
Adipose-derived mesenchymal stem cells (ASCs) accelerate the osteointegration of bone grafts and improve the efficiency in the formation of uniform bone tissue, providing a practical and clinically attractive approach in bone tissue regeneration. In this work, the effect of nanofibrous biomimetic matrices composed of poly(ε-caprolactone) (PCL), nanometric hydroxyapatite (nHA) particles and 14-3-3 protein isoform epsilon on the initial stages of human ASCs (hASCs) osteogenic differentiation was investigated. The cells were characterized by flow cytometry and induction to differentiation to adipogenic and osteogenic lineages. The isolated hASCs were induced to differentiate to osteoblasts over all scaffolds, and adhesion and viability of the hASCs were found to be similar. However, the activity of alkaline phosphatase (ALP) as early osteogenic marker in the PCL-nHA/protein scaffold was four times higher than in PCL-nHA and more than five times than the measured in neat PCL. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-09-03

3D Microcontact Printing for Combined Chemical and Topographical Patterning on Porous Cell Culture Membrane. - Borowiec, Justyna; Hampl, Joerg; Singh, Sukhdeep; Haefner, Sebastian; Friedel, Karin; Mai, Patrick; Brauer, Dana; Ruther, Florian; Liverani, Liliana; Boccaccini, Aldo R.; Schober, Andreas (ACS Applied Materials and Interfaces, 2018)
Micrometer-scale biochemical or topographical patterning is commonly used to guide the cell attachment and growth, but the ability to combine these patterns into an integrated surface with defined chemical and geometrical characteristics still remains a technical challenge. Here, we present a technical solution for simultaneous construction of 3D morphologies, in the form of channels, on porous membranes along with precise transfer of extracellular matrix proteins into the channels to create patterns with geometrically restricting features. By combining the advantages of microthermoforming and microcontact printing, this technique offers a unique patterning process that provides spatiotemporal control over morphological and chemical feature in a single step. By use of our 3D-microcontact printing (3DμCP), determined microstructures like channels with different depths and widths even with more complex patterns can be fabricated. Collagen, fibronectin, and laminin were successfully transferred inside the predesigned geometries, and the validity of the process was confirmed by antibody staining. Cells cultivated on 3DμCP patterned polycarbonate membrane have shown selective adhesion and growth. This technique offers a novel tool for creating freeform combinatorial patterning on the thermoformable surface.

acellular bioactivity of sol-gel derived borate glass-polycaprolactone electrospun scaffolds - Lepry, William C.; Smith, Sophia; Liverani, Liliana; Boccaccini, Aldo R.; Nazhat, Showan N. (Biomedical Glasses, 2016)
Recently, sol-gel derived borate glasses (BGs) have shown unprecedented conversion rates to bone-like mineral (hydroxycarbonated apatite). In an effort to explore their potential applications in bone tissue engineering, this study reports on the fabrication and characterization of BG particle incorporated electrospun "- polycaprolactone (PCL) fibrous composites. The electrospinning technique successfully incorporated PCL fibres with BG particles at 2.5 and 5 w/v%, with the higher BG loading creating a three-dimensional cotton-wool like morphology. Dynamic vapour sorption showed greater extents of mass change with BG content attributable to water sorption, and indicating greater reactivity in the composite systems. In vitro bioactivity was investigated in simulated body fluid for up to 7 days. Scanning electron microscopy, Fourier-transform infrared spectroscopy and x-ray diffraction indicated apatite formation in the 5 w/v% incorporated composite scaffold, which initiated as early as day 3. In summary, sol-gel derived BGs incorporated-fibrous electrospun PCL composites indicate rapid reactivity and bioactivity with potential applications in mineralized tissue engineering.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Bioactivity; Borate glass; Electrospinning; Mineralization; PCL; Scaffolds

A new generation of electrospun fibers containing bioactive glass particles for wound healing - Sergi, Rachele; Cannillo, Valeria; Boccaccini, Aldo R.; Liverani, Liliana (Materials, 2020)
Chitosan fibers blended with polyethylene oxide (CHIT_PEO) and crosslinked with genipin were fabricated by electrospinning technique. Subsequently, CHIT_PEO bioactive glass composite electrospun mats were fabricated with the aim to achieve flexible structures with adequate mechanical properties and improved biological performance respect to CHIT_PEO fibers, for potential applications in wound healing. Three different compositions of bioactive glasses (BG) were selected and investigated: 45S5 BG, a Sr and Mg containing bioactive glass (BGMS10) and a Zn-containing bioactive glass (BGMS_2Zn). Particulate BGs (particles size < 20 µm) were separately added to the starting CHIT_PEO solution before electrospinning. The two recently developed bioactive glasses (BGMS10 and BGMS_2Zn) showed very promising biological properties in terms of bioactivity and cellular viability; thus, such compositions were added for the first time to CHIT_PEO solution to fabricate composite electrospun mats. The incorporation of bioactive glass particles and their distribution into CHIT_PEO fibers were assessed by SEM and FTIR analyses. Furthermore, CHIT_PEO composite electrospun mats showed improved mechanical properties in terms of Young’s Modulus compared to neat CHIT_PEO fibers; on the contrary, the values of tensile strain at break (%) were comparable. Biological performance in terms of cellular viability was investigated by means of WST-8 assay and CHIT_PEO composite electrospun mats showed cytocompatibility and the desired cellular viability.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Bioactive glasses; Chitosan; Composite fibers; Electrospinning; Mechanical properties; Wound healing

Anti-inflammatory and antibacterial activities of cerium-containing mesoporous bioactive glass nanoparticles for drug-free biomedical applications - Kurtuldu, Fatih; Kankova, Hana; Beltrán, Ana M.; Liverani, Liliana; Galusek, Dusan; Boccaccini, Aldo R. (Materials Today Bio, 2021)
Mesoporous bioactive glass nanoparticles (MBGNPs) are attracting significant attention as suitable materials for multifunctional biomedical applications. In this study, cerium was incorporated into MBGNPs using two different approaches. In the first approach, cerium was added to the glass system directly during the synthesis, while in the second approach, cerium was added to the as-synthesized MBGNPs via the template ion-exchange method. The influence of the method of synthesis on the physicochemical properties of nanoparticles was examined by SEM, TEM, XRD, FTIR, and N2 adsorption-desorption analyses. The MBGNPs exhibited spheroidal morphology and disordered mesoporous structure. XRD analysis confirmed the amorphous nature of the nanoparticles. The chemical composition was determined by the acid digestion method using ICP-OES. The influence of the synthesis method on the specific surface area, mesoporosity, and solubility of synthesized nanoparticles in Tris/HCl (pH 7.4) and acetate (pH 4.5) buffer has also been studied. The obtained Ce containing MBGNPs were non-cytotoxic toward ​preosteoblast MC3T3-E1 cells in contact with nanoparticles in a concentration of up to 100 ​μg/mL. The anti-inflammatory effect of Ce containing MBGNPs was tested with lipopolysaccharides (LPS)-induced proinflammatory RAW 264.7 macrophage cells. Ce containing MBGNPs decreased the release of nitric oxide, indicating the anti-inflammatory response of macrophage cells. Ce containing MBGNPs also showed antibacterial activity against S. aureus and E. coli. The mentioned features of the obtained MBGNPs make them useful in a variety of biomedical applications, considering their biocompatibility, anti-inflammatory response, and enhanced antibacterial effect.
Keywords: Metal ion; Bioactive glassses; Nanoparticles; Anti-inflammation activity; Antibacterial materials

Article synthesis and characterization of mesoporous mg-and sr-doped nanoparticles for moxifloxacin drug delivery in promising tissue engineering applications - Pouroutzidou, Georgia K.; Liverani, Liliana; Theocharidou, Anna; Tsamesidis, Ioannis; Lazaridou, Maria; Christodoulou, Evi; Beketova, Anastasia; Pappa, Christina; Triantafyllidis, Konstantinos S.; Anastasiou, Antonios D.; Papadopoulou, Lambrini; Bikiaris, Dimitrios N.; et al. (International Journal of Molecular Sciences, 2021)
Mesoporous silica-based nanoparticles (MSNs) are considered promising drug carriers because of their ordered pore structure, which permits high drug loading and release capacity. The dissolution of Si and Ca from MSNs can trigger osteogenic differentiation of stem cells towards extracellular matrix calcification, while Mg and Sr constitute key elements of bone biology and metabolism. The aim of this study was the synthesis and characterization of sol–gel-derived MSNs codoped with Ca, Mg and Sr. Their physico-chemical properties were investigated by X-ray diffraction (XRD), scanning electron microscopy with energy dispersive X-ray analysis (SEM/EDX), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray fluorescence spectroscopy (XRF), Brunauer Emmett Teller and Brunauer Joyner Halenda (BET/BJH), dynamic light scattering (DLS) and ζ-potential measurements. Moxifloxacin loading and release profiles were assessed with high performance liquid chromatography (HPLC) cell viability on human periodontal ligament fibroblasts and their hemolytic activity in contact with human red blood cells (RBCs) at various concentrations were also investigated. Doped MSNs generally retained their textural characteristics, while different compositions affected particle size, hemolytic activity and moxifloxacin loading/release profiles. All co-doped MSNs revealed the formation of hydroxycarbonate apatite on their surface after immersion in simulated body fluid (SBF) and promoted mitochondrial activity and cell proliferation.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Drug loading/release; Human erythrocytes; Mesoporous nanoparticles; Moxifloxacin; Periodontal ligament cells

Assessment of in-vitro bioactivity, biodegradability and antibacterial activity of polymer-derived 3D printed åkermanite scaffolds - Dogrul, Fulden; Bednarzig, Vera; Elsayed, Hamada; Liverani, Liliana; Galusek, Dušan; Bernardo, Enrico; Boccaccini, Aldo R. (Open Ceramics, 2023)
Reticulated åkermanite (Ca2MgSi2O7) 3D scaffolds were fabricated by direct ink writing of pastes based on a commercial silicone resin and fillers, such as calcium carbonate (CaCO3) and magnesium hydroxide (Mg(OH)2) microparticles, followed by heat treatment at 1100 °C in air. To form liquid phase upon firing and thus promote the ionic interdiffusion, borax (Na2B4O7·10H2O) or hydrated sodium phosphate (Na2HPO4·12H2O) were considered as alternative additives. Although leading to scaffolds with different strength-to-density ratio, the two additives did not lead to substantial differences in terms of biological response. All fabricated ceramics exhibited acellular in-vitro bioactivity upon immersion in simulated-body-fluid (SBF) as well as antibacterial activity against S. aureus and E. coli. Direct contact cell viability test, performed with a stromal-cell line from mouse bone marrow (ST-2 cells), indicated no cytotoxicity of both samples determined by the WST-8 assay.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Antibacterial activity; Bioactivity; Bioceramic; Cytocompatibility; Direct ink writing (DIW); Polymer-derived-ceramic; Scaffold; Åkermanite

Bioactive behavior of mesoporous silica particle (MCM-41) coated bioactive glass-based scaffolds - Boccardi, Elena; Liverani, Liliana; Boccaccini, Aldo R. (International Journal of Applied Ceramic Technology, 2019)
A complete characterization of a novel family of multifunctional bioactive glass (45S5 composition) (BG)-based scaffolds for bone tissue engineering is presented. Scaffolds were developed via replication method of polyurethane packaging foam and natural marine sponge “Spongia Agaricina”. In order to increase the therapeutic functionality, the scaffolds were coated with mesoporous silica particles (MCM-41), which can act as drug delivery carrier, increase the bioactivity of the combined system and release Si ions, essential for the gene stimulation of osteoblast cells and for inducing new bone matrix formation. The MCM-41 particles were synthetized directly inside the scaffolds (CCM) or after the synthesis they were dispersed in ethanol and used for impregnation (PCM) of the scaffolds. The effect of the particles on the bioactivity of the scaffolds was assessed in simulated body fluid (SBF) for up to 7 days. The results indicate the possibility to obtain a multifunctional BG-scaffold system with enhanced bioactivity and reduced pH increase when in contact with physiological fluids.
CRIS-Team Scopus Importer:2019-05-02
Keywords: bioactive glass; bioactivity; scaffold

Biodegradabiliy of spherical mesoporous silica particles (MCM-41) in simulated body fluid (SBF) - Boccardi, Elena; Philippart, Anahi; Beltran, Ana M.; Schmidt, Jochen; Liverani, Liliana; Peukert, Wolfgang; Boccaccini, Aldo R. (American Mineralogist, 2018)
Keywords: Mesoporous silica particles; Simulated body fluid; Bone tissue engineering; Drug carriers; Biomaterials - Mineralogy Meets Medicine; Biodegradability

Biodegradable and bioactive polymer/inorganic phase composites - Kuth, Sonja; Liverani, Liliana (Elsevier, 2021)
In this chapter an overview of the main properties that could be tailored in composites for tissue engineering scaffolds applications are reported. The main approaches have been reviewed and developed for the fabrication of composites to introduce gradients and enhance bioactivity, mechanical properties, and interface tissue response in scaffolds. Moreover, an overview of the commonly used scaffold fabrication techniques used for composites and some selected applications of composite scaffolds are also presented.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bioactivity; Biodegradation; Composites

Bioengineered 3D ovarian model for long-term multiple development of preantral follicle: bridging the gap for poly(ε-caprolactone) (PCL)-based scaffold reproductive applications - Di Berardino, Chiara; Peserico, Alessia; Camerano Spelta Rapini, Chiara; Liverani, Liliana; Capacchietti, Giulia; Russo, Valentina; Berardinelli, Paolo; Ünalan, Irem; Damian-Buda, Andrada-Ioana; Boccaccini, Aldo R.; Barboni, Barbara (Reproductive Biology and Endocrinology, 2024)
Background: Assisted Reproductive Technologies (ARTs) have been validated in human and animal to solve reproductive problems such as infertility, aging, genetic selection/amplification and diseases. The persistent gap in ART biomedical applications lies in recapitulating the early stage of ovarian folliculogenesis, thus providing protocols to drive the large reserve of immature follicles towards the gonadotropin-dependent phase. Tissue engineering is becoming a concrete solution to potentially recapitulate ovarian structure, mostly relying on the use of autologous early follicles on natural or synthetic scaffolds. Based on these premises, the present study has been designed to validate the use of the ovarian bioinspired patterned electrospun fibrous scaffolds fabricated with poly(ε-caprolactone) (PCL) for multiple preantral (PA) follicle development. Methods: PA follicles isolated from lamb ovaries were cultured on PCL scaffold adopting a validated single-follicle protocol (Ctrl) or simulating a multiple-follicle condition by reproducing an artificial ovary engrafted with 5 or 10 PA (AO5PA and AO10PA). The incubations were protracted for 14 and 18 days before assessing scaffold-based microenvironment suitability to assist in vitro folliculogenesis (ivF) and oogenesis at morphological and functional level. Results: The ivF outcomes demonstrated that PCL-scaffolds generate an appropriate biomimetic ovarian microenvironment supporting the transition of multiple PA follicles towards early antral (EA) stage by supporting follicle growth and steroidogenic activation. PCL-multiple bioengineering ivF (AO10PA) performed in long term generated, in addition, the greatest percentage of highly specialized gametes by enhancing meiotic competence, large chromatin remodeling and parthenogenetic developmental competence. Conclusions: The study showcased the proof of concept for a next-generation ART use of PCL-patterned scaffold aimed to generate transplantable artificial ovary engrafted with autologous early-stage follicles or to advance ivF technologies holding a 3D bioinspired matrix promoting a physiological long-term multiple PA follicle protocol.
CRIS-Team Scopus Importer:2024-08-16
Keywords: in vitro folliculogenesis; in vitro oogenesis; Tissue engineering; Artificial-ovary; Preantral follicle development; Large chromatin remodeling; Oocyte maturation; Parthenogenetic activation; Embryo development; PCL-electrospun scaffold

Cerium and gallium containing mesoporous bioactive glass nanoparticles for bone regeneration: Bioactivity, biocompatibility and antibacterial activity - Kurtuldu, Fatih; Mutlu, Nurshen; Michálek, Martin; Zheng, Kai; Masar, Milan; Liverani, Liliana; Chen, Si; Galusek, Dušan; Boccaccini, Aldo R. (Materials Science and Engineering C, 2021)
In recent years, mesoporous bioactive glass nanoparticles (MBGNPs) have generated great attention in biomedical applications. In this study, cerium and gallium doped MBGNPs were prepared by microemulsion assisted sol-gel method in the binary SiO2-CaO system. MBGNPs with spheroidal and pineal shaped morphology were obtained. Nitrogen sorption analysis elucidated the mesoporous structure of synthesized nanoparticles with high specific surface area. X-ray diffraction analysis confirmed the amorphous nature of the nanoparticles. The chemical compositions of all samples were determined by inductively coupled plasma-optical emission spectrometry (ICP-OES), which revealed that the contents of cerium and gallium could be tailored by adjusting the concentrations of the precursors used for the synthesis. All MBGNPs exhibited in vitro bioactivity when immersed in simulated body fluid, except the particles doped with higher amounts than 1 mol% of cerium. MBGNPs showed antibacterial activity against S. aureus and E. coli without exhibiting cytotoxicity towards MG-63 osteoblast-like cells. Mentioned features of the obtained Ce and Ga-doped MBGNPs make them useful for multifunctional applications such as drug delivery carriers or bioactive fillers for bone tissue engineering applications.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Antibacterial activity; Cerium; Gallium; Mesoporous bioactive glass nanoparticles; Sol-gel method

Comparative Study of the Antimicrobial Activity of Selenium Nanoparticles With Different Surface Chemistry and Structure - Filipović, Nenad; Ušjak, Dušan; Milenković, Marina T.; Zheng, Kai; Liverani, Liliana; Boccaccini, Aldo R.; Stevanović, Magdalena M. (Frontiers in Bioengineering and Biotechnology, 2021)
Although selenium nanoparticles (SeNPs) have gained attention in the scientific community mostly through investigation of their anticancer activity, a great potential of this nanomaterial was recognized recently regarding its antimicrobial activity. The particle form, size, and surface chemistry have been recognized as crucial parameters determining the interaction of nanomaterials with biological entities. Furthermore, considering a narrow boundary between beneficial and toxic effects for selenium per se, it is clear that investigations of biomedical applications of SeNPs are very demanding and must be done with great precautions. The goal of this work is to evaluate the effects of SeNPs surface chemistry and structure on antimicrobial activity against several common bacterial strains, including Staphylococcus aureus (ATCC 6538), Enterococcus faecalis (ATCC 29212), Bacillus subtilis (ATCC 6633), and Kocuria rhizophila (ATCC 9341), as well as Escherichia coli (ATCC 8739), Salmonella Abony (NCTC 6017), Klebsiella pneumoniae (NCIMB 9111) and Pseudomonas aeruginosa (ATCC 9027), and the standard yeast strain Candida albicans (ATCC 10231). Three types of SeNPs were synthesized by chemical reduction approach using different stabilizers and reducing agents: (i) bovine serum albumin (BSA) + ascorbic acid, (ii) chitosan + ascorbic acid, and (iii) with glucose. A thorough physicochemical characterization of the obtained SeNPs was performed to determine the effects of varying synthesis parameters on their morphology, size, structure, and surface chemistry. All SeNPs were amorphous, with spherical morphology and size in the range 70–300 nm. However, the SeNPs obtained under different synthesis conditions, i.e. by using different stabilizers as well as reducing agents, exhibited different antimicrobial activity as well as cytotoxicity which are crucial for their applications. In this paper, the antimicrobial screening of the selected systems is presented, which was determined by the broth microdilution method, and inhibitory influence on the production of monomicrobial and dual-species biofilm was evaluated. The potential mechanism of action of different systems is proposed. Additionally, the cytotoxicity of SeNPs was examined on the MRC-5 cell line, in the same concentration interval as for antimicrobial testing. It was shown that formulation SeNPs-BSA expressed a significantly lower cytotoxic effect than the other two formulations.
CRIS-Team Scopus Importer:2021-02-26
Keywords: antimicrobial activity; dual-species biofilm; inhibition of biofilms; nanocomposites; selenium nanoparticles (SeNPs)

Copper-doped cotton-like malleable electrospun bioactive glass fibers for wound healing applications - Liverani, Liliana; Reiter, Theresa; Zheng, Kai; Neščáková, Zuzana; Boccaccini, Aldo R. (Materials Letters: X, 2022)
The combination of electrospinning and sol-gel methods is attracting the interest of the scientific community for developing three-dimensional bioactive glass (BG)-based fibers. This paper reports the fabrication of cotton-like copper-doped BG fibers by combining electrospinning and sol-gel techniques. Acellular bioactivity in simulated body fluid, ion release, cell viability and scratch cell tests were performed. Results showed that copper was successfully incorporated in the fibers and Cu ions were released in limited concentration over seven days. The presence of copper delayed the mineralization of the fibers upon immersion in simulated body fluid (SBF), but it did not affect keratinocyte viability and migration. Wound closure in the scratch cell test was achieved in 48 h for all the investigated samples.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Bioactive glass; Copper; Electrospinning; Sol-gel; Wound healing

Cotton-wool-like borosilicate glass fibers for tissue regeneration: Preparation, characterization and in vitro bioactivity - Sengupta, Susanta; Liverani, Liliana; Galusek, Dušan; Boccaccini, Aldo R. (Open Ceramics, 2023)
Borosilicate (60SiO2-20CaO-16B2O3-4P2O5) glass fibers (BSGF) were fabricated by electrospinning in combination with sol-gel processing. BSGF were calcined at 600, 700 and 800 °C to remove the polymeric binder and optimize the formation of the inorganic phase. HCA (hydroxycarbonate apatite) was formed on BSGF within 24h of immersion in simulated body fluid (SBF), which was confirmed by XRD and FTIR analyses. In vitro cytotoxicity was measured with mouse osteoblast and fibroblast cell lines. WST-8 assay and fluorescence images confirmed the non-cytotoxic nature of the BSGF which did not induce any adverse effect on the cell activity.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Bioactive glass; Electrospinning; Sol-gel

Cotton wool-like ion-doped bioactive glass nanofibers: investigation of Zn and Cu combined effect - Ünalan, Irem; Rimoli, Ian Heit; Mutlu, Nurshen; Michálek, Martin; Abraham, Gustavo A.; Liverani, Liliana; Boccaccini, Aldo R. (Biomedical Materials (Bristol), 2024)
Electrospinning is a versatile and straightforward technique to produce nanofibrous mats with different morphologies. In addition, by optimizing the solution, processing, and environmental parameters, three-dimensional (3D) nanofibrous scaffolds can also be created using this method. In this work, the preparation and characterization of bioactive glass (BG) scaffolds based on the SiO2-CaO sol-gel system, a biomaterial with a highly reactive surface, is reported. The electrospinning technique was combined with sol-gel methods to obtain nanofibrous 3D cotton wool-like scaffolds. The addition of zinc and copper ions to the silica-calcia system was examined, and the influence of these ions on the material properties and characteristics was investigated by various characterization techniques, from morphological and chemical properties to antibacterial and wound closure capability, cell viability and ion release. Our findings show that the cotton wool-like ion-doped nanofibers are promising for wound healing applications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: copper; cotton wool-like electrospun nanofibers; sol-gel synthesis; wound healing; zinc

Development of a bioactive glass-polymer composite for wound healing applications - Moura, D.; Souza, M. T.; Liverani, Liliana; Rella, Giulia; Luz, G. M.; Mano, J. F.; Boccaccini, Aldo R. (Materials Science and Engineering C, 2017)
Keywords: Bioactive glass; Electrospinning; Mineralization; PCL; Wound healing

Effect of benign solvents composition on poly(epsilon-caprolactone) electrospun fiber properties - Bongiovanni Abel, Silvestre; Liverani, Liliana; Boccaccini, Aldo R.; Abraham, Gustavo A. (Materials Letters, 2019)
Green electrospinning is a flourishing trend in the field of electrospinning (ES) of polymeric/composite materials for biomedical applications. The use of non-toxic solvents instead of the most commonly used solvents in electrospinning is needed to avoid the possible presence toxic solvents traces in the electrospun mats, enhancing their cytocompatibility. It was found that a single solvent or solvent mixtures have a critical role in fiber formation and properties. In this work, fibers in the micro/nanoscale were obtained by electrospinning technique from different poly(epsilon-caprolactone) (PCL) solutions. Benign solvents (i.e. acetic and formic acids, water and their mixtures) and standard organic solvents for ES (i.e. chloroform) were explored in order to compare the fiber characteristics and properties. Morphology, size, crystallinity, thermal and polymer stability of fibers were analyzed. The obtained results showed the suitability of the use of benign solvents for ES, highlighting that for the use of formic acid the degradation of PCL should be taken into consideration. (C) 2019 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2019-04-04

Effect of glycerol and H3PO4 on the bioactivity and degradability of rod-like SBA-15 particles with active surface for bone tissue engineering applications - Vargas-Osorio, Zulema; Klotschan, Artem; Arango Ospina, Marcela; Piñeiro, Yolanda; Liverani, Liliana; Rivas, José; Michálek, Martin; Galusek, Dušan; Boccaccini, Aldo R. (Microporous and Mesoporous Materials, 2022)
In the quest to increase the quality of life and life expectancy, there is a great demand to develop advanced medical devices capable of facing current health challenges. Santa Barbara Amorphous (SBA-15) mesoporous silica has been demonstrated to be a remarkable option for a variety of biomedical applications, from tissue engineering to drug delivery, due to its unique hierarchical porous structure. This work reports on the effect of using different ratios and concentrations of an acid mixture mediated by HCl/H3PO4 that in combination with a glycerol-modified silane precursor favoured obtaining bioactive SBA-15 mesoporous silica rods. The surfactant was removed by solvent extraction which allowed to keep a substantial amount of silanol groups (SiOH) at the surface. All the evaluated samples showed homogeneous rod shape and particle size, as well as high bioactivity after being immersed for 14 days in simulated body fluid (SBF). Different structural arrangements of needle-type carbonate hydroxyapatite (HCA) crystals were produced from SBA-15 upon immersion in SBF. By scanning electron microscopy (SEM) characterization, it was observed that rod-shaped SBA-15 materials displayed higher degradability when the concentration of H3PO4 was increased. An indirect cell viability assay with MC3T3-E1 osteoblast precursor cells was performed by incubating cells in cell culture medium exposed to SBA-15 particles for 1 and 4 days. The results obtained from the WST-8 assay and fluorescent staining showed no negative effect on cell viability, indicating a lack of cytotoxicity of the rod-like SBA-15 particles.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Bioactivity; Cytocompatibility; Degradability; Rod-like SBA-15 particles; Solvents extraction

Effect of Zn and Ga doping on bioactivity, degradation, and antibacterial properties of borate 1393-B3 bioactive glass - Mutlu, Nurshen; Kurtuldu, Fatih; Ünalan, Irem; Neščáková, Zuzana; Kaňková, Hana; Galusková, Dagmar; Michálek, Martin; Liverani, Liliana; Galusek, Dušan; Boccaccini, Aldo R. (Ceramics International, 2022)
Borate 1393-B3 bioactive glasses doped with ZnO or Ga2O3 (1, 3, and 6% mol) were produced by conventional melt quenching. All doped glasses showed in-vitro bioactivity in simulated body fluid (SBF). For the first time, the dissolution behavior of the glasses both in phosphate-buffered saline (PBS) and cell culture medium was investigated. The ion release rate in the cell culture medium increased compared to that in PBS solution. All tested glass compositions, including the parent 1393-B3 glass, showed antibacterial effect against S. aureus and E. coli. The incorporation of Zn and Ga enhanced the viability of MG-63 osteoblast-like cells compared to the base 1393-B3 glass. The results show the potential of Zn and Ga-doped borate glasses in multifunctional tissue engineering applications.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Antibacterial activity; Bioactive glasses; Borate glasses; Gallium; Zinc

Electrospinning of cotton-like fibers based on cerium-doped sol–gel bioactive glass - Lu, Hsuan-Heng; Zheng, Kai; Boccaccini, Aldo R.; Liverani, Liliana (Materials Letters, 2023)
In this study, Ce-doped calcium silicate-based bioactive glass sols were electrospun under well-defined parameters and heat-treated to obtain cotton-like fibrous structures. The 3D structures comprised long and entangled fibers with interconnected pores, and the successful incorporation of Ce was confirmed by EDX analysis. The fibers were highly hydrophilic and demonstrated in vitro bioactivity after immersion in simulated body fluid. The fibers were non-cytotoxic toward keratinocytes and did not inhibit the wound closure process, which was characterized in vitro.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Bioactive glass; Electrospinning; Fibers; Sol-gel; Wound healing

Electrospun fibers of poly(butylene succinate–co–dilinoleic succinate) and its blend with poly(glycerol sebacate) for soft tissue engineering applications - Liverani, Liliana; Piegat, Agnieszka; Niemczyk, Agata; El Fray, Miroslawa; Boccaccini, Aldo R. (European Polymer Journal, 2016)
Keywords: Electrospinning; Poly(butylene succinate-dilinoleic succinate); Poly(glycerol sebacate); Soft tissue engineering

Electrospun Filaments Embedding Bioactive Glass Particles with Ion Release and Enhanced Mineralization - Serio, Francesca; Miola, Marta; Verne, Enrica; Pisignano, Dario; Boccaccini, Aldo R.; Liverani, Liliana (Nanomaterials, 2019)
Efforts in tissue engineering aim at creating scaffolds that mimic the physiological environment with its structural, topographical and mechanical properties for restoring the function of damaged tissue. In this study we introduce composite fibres made by a biodegradable poly(lactic acid) (PLLA) matrix embedding bioactive silica-based glass particles (SBA2). Electrospinning is performed to achieve porous PLLA filaments with uniform dispersion of bioactive glass powder. The obtained composite fibres show in aligned arrays significantly increased elastic modulus compared with that of neat polymer fibres during uniaxial tensile stress. Additionally, the SBA2 bioactivity is preserved upon encapsulation as highlighted by the promoted deposition of hydroxycarbonate apatite (HCA) upon immersion in simulated body fluid solutions. HCA formation is sequential to earlier processes of polymer erosion and ion release leading to acidification of the surrounding solution environment. These findings suggest PLLA-SBA2 fibres as a composite, multifunctional system which might be appealing for both bone and soft tissue engineering applications.
CRIS-Team WoS Importer:2019-03-29

Electrospun patterned porous scaffolds for the support of ovarian follicles growth: a feasibility study - Liverani, Liliana; Amir, Fattahi; Raffel, Nathalie; Preis, Alexander; Hoffmann, Inge; Boccaccini, Aldo R.; Beckmann, Matthias; Dittrich, Ralf (Scientific Reports, 2019)
Recently, the interest of the scientific community is focused on the application of tissue engineering approach for the fertility restoration. In this paper innovative patterned electrospun fibrous scaffolds were fabricated and used as 3D system for porcine follicles culture. The obtained scaffolds demonstrated to be a suitable support which did not alter or interfere with the typical spherical follicles morphology. The fibrillar structure of the scaffolds mimics the morphology of the healthy native tissue. The use of porcine follicles implied many advantages respect to the use of mouse model. Relevant results showed that more than the scaffold pattern and struts dimension, the selection of proper biomaterials improve the follicles adhesion and development.
CRIS-Team WoS Importer:2019-02-21

Electrospun PCL fiber mats incorporating multi-targeted B and Co Co-doped bioactive glass nanoparticles for angiogenesis - Chen, Si; Galusková, Dagmar; Kaňková, Hana; Zheng, Kai; Michálek, Martin; Liverani, Liliana; Galusek, Dušan; Boccaccini, Aldo R. (Materials, 2020)
Vascularization is necessary in tissue engineering to keep adequate blood supply in order to maintain the survival and growth of new tissue. The synergy of biologically active ions with multi-target activity may lead to superior angiogenesis promotion in comparison to single-target approaches but it has been rarely investigated. In this study, polycaprolactone (PCL) fiber mats embedded with B and Co co-doped bioactive glass nanoparticles (BCo. BGNs) were fabricated as a tissue regeneration scaffold designed for promoting angiogenesis. BCo. NBGs were successfully prepared with well-defined spherical shape using a sol-gel method. The PCL fiber mats embedding co-doped bioactive glass nanoparticles were fabricated by electrospinning using benign solvents. The Young's moduli of the nanoparticle containing PCL fiber mats were similar to those of the neat fiber mats and suitable for scaffolds utilized in soft tissue repair approaches. The mats also showed non-cytotoxicity to ST-2 cells. PCL fiber mats containing BCo. BGNs with a relatively high content of B and Co promoted the secretion of vascular endothelial growth factor to a greater extent than PCL fiber mats with a relatively low B and Co contents, which demonstrates the potential of dual ion release (B and Co) from bioactive glasses to enhance angiogenesis in soft tissue engineering.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Angiogenesis; Bioactive glasses; Electrospinning; Sol-gel method; Tissue regeneration

Electrospun PCL/PGS composite fibers incorporating bioactive glass particles for soft tissue engineering applications - Luginina, Marina; Schuhladen, Katharina; Orrú, Roberto; Cao, Giacomo; Boccaccini, Aldo R.; Liverani, Liliana (Nanomaterials, 2020)
Poly(glycerol-sebacate) (PGS) and poly(epsilon caprolactone) (PCL) have been widely investigated for biomedical applications in combination with the electrospinning process. Among others, one advantage of this blend is its suitability to be processed with benign solvents for electrospinning. In this work, the suitability of PGS/PCL polymers for the fabrication of composite fibers incorporating bioactive glass (BG) particles was investigated. Composite electrospun fibers containing silicate or borosilicate glass particles (13-93 and 13-93BS, respectively) were obtained and characterized. Neat PCL and PCL composite electrospun fibers were used as control to investigate the possible effect of the presence of PGS and the influence of the bioactive glass particles. In fact, with the addition of PGS an increase in the average fiber diameter was observed, while in all the composite fibers, the presence of BG particles induced an increase in the fiber diameter distribution, without changing significantly the average fiber diameter. Results confirmed that the blended fibers are hydrophilic, while the addition of BG particles does not affect fiber wettability. Degradation test and acellular bioactivity test highlight the release of the BG particles from all composite fibers, relevant for all applications related to therapeutic ion release, i.e., wound healing. Because of weak interface between the incorporated BG particles and the polymeric fibers, mechanical properties were not improved in the composite fibers. Promising results were obtained from preliminary biological tests for potential use of the developed mats for soft tissue engineering applications.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Benign solvents; Bioactive glass; Composite fibers; Electrospinning; Poly(glycerol-sebacate)

ELECTROSPUN SCAFFOLDS FOR OVARIAN TISSUE ENGINEERING: KEY POINTS OF SCAFFOLD-FOLLICLES INTERACTIONS - Liverani, Liliana; Bleisinger, Nathalie; Hoffmann, Inge; Beckmann, Matthias; Dittrich, Ralf; Boccaccini, Aldo R. (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Electrospun Zein Fibers Incorporating Poly(glycerol sebacate) for Soft Tissue Engineering. - Vogt, Lena; Liverani, Liliana; Roether, Judith; Boccaccini, Aldo R. (Nanomaterials, 2018)
For biomedical applications such as soft tissue engineering, plant proteins are becoming increasingly attractive. Zein, a class of prolamine proteins found in corn, offers excellent properties for application in the human body, but has inferior mechanical properties and lacks aqueous stability. In this study, electrospun scaffolds from neat zein and zein blended with prepolymer and mildly cross-linked poly(glycerol sebacate) (PGS) were fabricated. Less toxic solvents like acetic acid and ethanol were used. The morphological, physiochemical and degradation properties of the as-spun fiber mats were determined. Neat zein and zein-PGS fiber mats with high zein concentration (24 wt % and 27 wt %) showed defect-free microstructures. The average fiber diameter decreased with increasing PGS amount from 0.7 ± 0.2 µm to 0.09 ± 0.03 µm. The addition of PGS to zein resulted in a seven-fold increase in ultimate tensile strength and a four-fold increase in failure strain, whereas the Young’s Modulus did not change significantly. Degradation tests in phosphate buffered saline revealed the morphological instability of zein containing fiber mats in contact with aqueous media. Therefore, the fibers were in situ cross-linked with N-(3-Dimethylaminopropyl)-N′-ethylcarbodiimide (EDC)/N-Hydroxysuccinimide (NHS), which led to improved morphological stability in aqueous environment. The novel fibers have suitable properties for application in soft tissue engineering.
Keywords: zein; poly(glycerol sebacate); electrospinning; nano-fibers; soft tissue engineering

Environmentally friendly fabrication of electrospun nanofibers made of polycaprolactone, chitosan and k-carrageenan (PCL/CS/k-C) - Vargas Osorio, Zulema; Ruther, Florian; Chen, Si; Sengupta, Susanta; Liverani, Liliana; Michalek, Martin; Galusek, Dušan; Boccaccini, Aldo R. (Biomedical Materials, 2022)
Electrospun fibers based on biodegradable polyanionic or polycationic biopolymers are highly beneficial for biomedical applications. In this work, electrospun nanofibers made from poly(epsilon caprolactone) (PCL), chitosan (CS) and k-carrageenan (k-C) were successfully fabricated using several mixtures of benign solvents containing formic acid and acetic acid. The addition of k-C improved the preparation procedure for the production of PCL/CS fibers by electrospinning. Moreover, a polymer mixture was selected to be stored at -20 degrees C for one month with the purpose to study the properties of the resulting fiber mat. The results indicated that fiber characteristics were not seriously compromised compared to the ones of those fabricated with the original solution, which represents an important reduction in produced waste. Thus, the interactions that occur between positively and negatively charged hydrophilic polysaccharides might induce higher stability to the linear aliphatic polyester in the polymer mixture. All fiber mats were morphologically, physico-chemically and mechanically characterized, showing average fiber diameters in the nano scale. A direct cell viability assay using ST-2 cells demonstrated cell proliferation after seven days of incubation for all prepared fiber mats, confirming their suitability as potential candidates for bone tissue engineering and wound healing applications.
CRIS-Team WoS Importer:2022-06-17

Female reproductive organs tissue engineering - Liverani, Liliana; Bleisinger, Nathalie; Beckmann, Matthias; Dittrich, Ralf (Elsevier, 2021)
The present chapter is focused on the tissue engineering approach applied to female reproductive organs. This field was quite often presented as urogenital applications, but recently the interest of the scientific community has been more oriented on the reproductive organs and to the evaluation of tissue engineering-based approaches focusing on the selection of biomaterials and scaffold fabrication technologies to develop suitable biomimetic three-dimensional constructs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biomaterials; Fallopian tubes; Ovary; Reproductive organs; REPROTEN; Tissue engineering; Uterus

Fertility Preservation: Optimization of Follicle Extraction before Cultivation in the Artificial Ovary - Keckstein, P.; Fattahi, Amir; Liverani, Liliana; Dittrich, Ralf; Hoffmann, I; Boccaccini, Aldo R.; Beckmann, Matthias; Bleisinger, Nathalie (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Fibronectin Functionalized Electrospun Fibers by Using Benign Solvents: Best Way to Achieve Effective Functionalization - Liverani, Liliana; Killian, Manuela; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2019)
The aim of this study is to demonstrate the feasibility of different functionalization methods for electrospun fibers developed using benign solvents. In particular three different approaches were investigated to achieve the functionalization of poly(epsilon caprolactone) (PCL) electrospun fibers with fibronectin. Protein surface entrapment, chemical functionalization and coaxial electrospinning were performed and compared. Moreover, bilayered scaffolds, with a top patterned and functionalized layer with fibronectin and a randomly oriented not functionalized layer were fabricated, demonstrating the versatility of the use of benign solvents for electrospinning also for the fabrication of complex graded structures. Besides the characterization of the morphology of the obtained scaffolds, ATR-FTIR and ToF-SIMS were used for the surface characterization of the functionalized fibers. Cell adhesion and proliferation were also investigated by using ST-2 cells. Positive results were obtained from all functionalized scaffolds and the most promising results were obtained with bilayered scaffolds, in terms of cells infiltration inside the fibrous structure.
CRIS-Team WoS Importer:2019-04-16

Functional behavior of chitosan/gelatin/silica-gentamicin coatings by electrophoretic deposition on surgical grade stainless steel - Aydemir, Tuba; Liverani, Liliana; Pastore, Juan I.; Ceré, Silvia M.; Goldmann, Wolfgang; Boccaccini, Aldo R.; Ballarre, Josefina (Materials Science and Engineering C, 2020)
Metals are used in several orthopedic applications as fixation elements for the stabilization of fractures or as prostheses. One of the most common orthopedic biomaterials in many developing countries is surgical grade stainless steel (SS). However, its use as permanent implant in orthopedic surgery is conditioned due to its limited corrosion resistance in physiological media, lack of osseointegration, and absence of antibacterial effect. The aim of this work is to generate a degradable coating with antibacterial properties for stainless steel to be used in implants/medical devices. The coating is composed of a biopolymer/silica-gentamicin nanoparticles composite obtained by electrophoretic deposition (EPD) on surgical grade stainless steel plates. The coating surface was characterized by microscopic examination, and in vitro performance was evaluated after immersion in phosphate-buffered saline (PBS) solution, simulated body fluid (SBF), and cell culture medium, to analyze coating degradation, antibiotics release, cell attachment (ST-2 stromal cells), and antibacterial (Escherichia coli and Staphylococcus aureus) properties. EPD coatings were uniform and covered homogeneously the surface of the SS substrate. Also the distribution of silica-gentamicin nanoparticles was homogeneous on the coated area. The degradation of the chitosan-gelatin coatings was evident after 7 days of immersion. The gentamicin release led to excellent antibacterial behavior at 24 h, meanwhile the cell proliferation (at 7 days culture) was not inhibited. The results show that the coating system exhibits promising behavior which could contribute to prevent hospital infections at early implantation times.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Chitosan; Electrophoretic deposition; Gelatin; Prevention of infections; Silica-gentamicin nanoparticles; Stainless steel implants

Gallium-containing mesoporous nanoparticles influence in-vitro osteogenic and osteoclastic activity - Kurtuldu, Fatih; Mutlu, Nurshen; Friedrich, Ralf P.; Beltrán, Ana M.; Liverani, Liliana; Detsch, Rainer; Alexiou, Christoph; Galusek, Dušan; Boccaccini, Aldo R. (Biomaterials Advances, 2024)
Mesoporous silica nanoparticles were synthesized using a microemulsion-assisted sol-gel method, and calcium, gallium or a combination of both, were used as dopants. The influence of these metallic ions on the physicochemical properties of the nanoparticles was investigated by scanning and transmission electron microscopy, as well as N2 adsorption-desorption methods. The presence of calcium had a significant impact on the morphology and textural features of the nanoparticles. The addition of calcium increased the average diameter of the nanoparticles from 80 nm to 150 nm, while decreasing their specific surface area from 972 m2/g to 344 m2/g. The nanoparticles of all compositions were spheroidal, with a disordered mesoporous structure. An ion release study in cell culture medium demonstrated that gallium was released from the nanoparticles in a sustained manner. In direct contact with concentrations of up to 100 μg/mL of the nanoparticles, gallium-containing nanoparticles did not exhibit cytotoxicity towards pre-osteoblast MC3T3-E1 cells. Moreover, in vitro cell culture tests revealed that the addition of gallium to the nanoparticles enhanced osteogenic activity. Simultaneously, the nanoparticles disrupted the osteoclast differentiation of RAW 264.7 macrophage cells. These findings suggest that gallium-containing nanoparticles possess favorable physicochemical properties and biological characteristics, making them promising candidates for applications in bone tissue regeneration, particularly for unphysiological or pathological conditions such as osteoporosis.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Bioactive glasses; Gallium; Mesoporous silica nanoparticles; Osteoblast; Osteoclast

Hierarchical multi-layered scaffolds based on electrofluidodynamic processes for tissue engineering - Piegat, Agnieszka; Niemczyk, Agata; Boccaccini, Aldo R.; El Fray, Miroslawa; Liverani, Liliana (Biomedical Materials, 2021)
The aim of this study was to obtain hierarchical scaffolds combining 3D printing and two electrofluidodynamic methods. The multi-layered scaffold is composed by 3D printed struts, electrospun fibers obtained from poly(epsilon-caprolactone) and electrosprayed spheres produced from hydrophobically modified chitosan, namely chitosan grafted with linoleic acid (CHLA). Since CHLA has been used for the first time in the electrospraying (electro dynamic spraying, EDS) process, the formation of spheres needed an optimization process. The EDS process was strongly affected by the solvent mixture composition, concentration of acid used for CHLA dissolution and solution flow rate. By using the optimized electrospraying conditions, uniformly distributed spheres have been obtained, decorating struts and nanofibers. Preliminary biological tests with mouse preosteoblasts (MC3T3-E1) were performed to investigate the effect of the hierarchical scaffold on cell seeding efficacy. Results showed that the hierarchical structure enhances cell seeding efficacy, respect to the 3D printed struts alone, preventing that the cells passed through the struts during the seeding. Moreover, the addition of the electrosprayed nanoparticles does not affect the cell seeding efficiency. The versatility of the proposed structure, with the added value of CHLA nanoparticles decoration could be suitable for several applications in tissue engineering, mainly related to drug delivery systems.
CRIS-Team WoS Importer:2021-04-02

Impact of electrospun scaffold topology on the performance of in-vitro Folliculogenesis applied to preantral ovine follicles - Di Berardino, C.; Liverani, Liliana; Capacchietti, G.; Peserico, A.; Boccaccini, Aldo R.; Barboni, B. (HUMAN REPRODUCTION, 2022)
CRIS-Team WoS Importer:2022-10-21

Incorporation of bioactive glasses containing Mg, Sr, and Zn in electrospun PCL fibers by using benign solvents - Sergi, Rachele; Cannillo, Valeria; Boccaccini, Aldo R.; Liverani, Liliana (Applied Sciences, 2020)
Poly(ε-caprolactone) (PCL) and PCL/bioactive glass composite fiber mats were produced by electrospinning technique. To improve cell adhesion and proliferation (i) 45S5, (ii) a bioactive glass containing strontium and magnesium oxides, and (iii) a bioactive glass containing zinc oxide were separately added to the starting PCL solution before electrospinning. A good incorporation of bioactive glass particles in PCL electrospun mats was confirmed by SEM and FTIR analyses. Bioactivity was evaluated by immersion of PCL mats and PCL/bioactive glass electrospun fiber mats in simulated body fluid (SBF). Bone murine stromal cells (ST-2) were employed in WST-8 assay to assess cell viability, cell morphology, and proliferation. The results showed that the presence of bioactive glass particles in the fibers enhances cell adhesion and proliferation compared to neat PCL mats. Furthermore, PCL/bioactive glass electrospun mats showed higher wound-healing rate (measured as cell migration rate) in vitro compared to neat PCL electrospun mats. Therefore, the characteristics of the PCL matrix combined with biological properties of bioactive glasses make PCL/bioactive glass composite ideal candidate for biomedical application.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Bioactive glass; Composite; Electrospinning; PCL; Wound healing

Incorporation of bioactive glass nanoparticles in electrospun PCL/chitosan fibers by using benign solvents - Liverani, Liliana; Lacina, Jonas; Roether, Judith; Boccardi, Elena; Killian, Manuela; Schmuki, Patrik; Schubert, Dirk W.; Boccaccini, Aldo R. (Bioactive Materials, 2018)

Incorporation of calcium containing mesoporous (MCM-41-type) particles in electrospun PCL fibers by using benign solvents - Liverani, Liliana; Boccardi, Elena; Maria Beltran, Ana; Boccaccini, Aldo R. (Polymers, 2017)
Keywords: Benign solvents; Composites; Electrospinning; Mesoporous silica calcium containing MCM-41; Nanofibers; Poly(epsilon-caprolactone)

In vitro degradation and bioactivity of composite poly-l-lactic (PLLA)/bioactive glass (BG) scaffolds: comparison of 45S5 and 1393BG compositions - Conoscenti, Gioacchino; Pavia, Francesco Carfi; Ciraldo, Francesca; Liverani, Liliana; Brucato, Valerio; La Carrubba, Vincenzo; Boccaccini, Aldo R. (Journal of Materials Science, 2018)

IVM Advances for Early Antral Follicle-Enclosed Oocytes Coupling Reproductive Tissue Engineering to Inductive Influences of Human Chorionic Gonadotropin and Ovarian Surface Epithelium Coculture - Peserico, Alessia; Di Berardino, Chiara; Capacchietti, Giulia; Camerano Spelta Rapini, Chiara; Liverani, Liliana; Boccaccini, Aldo R.; Russo, Valentina; Mauro, Annunziata; Barboni, Barbara (International Journal of Molecular Sciences, 2023)
In vitro maturation (IVM) is not a routine assisted reproductive technology (ART) for oocytes collected from early antral (EA) follicles, a large source of potentially available gametes. Despite substantial improvements in IVM in the past decade, the outcomes remain low for EA-derived oocytes due to their reduced developmental competences. To optimize IVM for ovine EA-derived oocytes, a three-dimensional (3D) scaffold-mediated follicle-enclosed oocytes (FEO) system was compared with a validated cumulus-oocyte complex (COC) protocol. Gonadotropin stimulation (eCG and/or hCG) and/or somatic cell coculture (ovarian vs. extraovarian-cell source) were supplied to both systems. The maturation rate and parthenogenetic activation were significantly improved by combining hCG stimulation with ovarian surface epithelium (OSE) cells coculture exclusively on the FEO system. Based on the data, the paracrine factors released specifically from OSE enhanced the hCG-triggering of oocyte maturation mechanisms by acting through the mural compartment (positive effect on FEO and not on COC) by stimulating the EGFR signaling. Overall, the FEO system performed on a developed reproductive scaffold proved feasible and reliable in promoting a synergic cytoplasmatic and nuclear maturation, offering a novel cultural strategy to widen the availability of mature gametes for ART.
CRIS-Team Scopus Importer:2023-04-21
Keywords: early antral follicle; EGF signaling; follicle-enclosed oocyte; human chorionic gonadotropin; in vitro oocyte maturation; ovarian surface epithelium; PCL electrospun scaffold; sheep

Manuka honey and bioactive glass impart methylcellulose foams with antibacterial effects for wound-healing applications - Schuhladen, Katharina; Mukoo, Pratishtha; Liverani, Liliana; Nescakova, Zuzana; Boccaccini, Aldo R. (Biomedical Materials, 2020)
Wound dressings able to deliver topically bioactive molecules represent a new generation of wound-regeneration therapies. In this article, foams based on methylcellulose cross-linked with Manuka honey were used as a platform to deliver borate bioactive glass particles doped additionally with copper. Borate bioactive glasses are of great interest in wound-healing applications due to a combination of favorable features, such as angiogenic and antibacterial properties. The multifunctional composite providing the dual effect of the bioactive glass and Manuka honey was produced by freeze-drying, and the resulting foams exhibit suitable morphology characterized by high porosity. Moreover, the performed tests showed improved wettability and mechanical performance with the addition of bioactive glass particles. Dissolution studies using simulated body fluid and cell biology tests using relevant skin cells further proved the excellent bioactivity and positive effects of the foams on cell proliferation and migration. Most interestingly, by the dual release of Manuka honey and ions from the copper-doped bioactive glass, an antibacterial effect againstE. coliandS. aureuswas achieved. Therefore, the multifunctional foams showed promising outcomes as potential wound dressings for the treatment of infected wounds.
CRIS-Team WoS Importer:2020-10-16

Mesoporous silica submicron particles (MCM-41) incorporating nanoscale Ag: synthesis, characterization and application as drug delivery coatings - Boccardi, Elena; Liverani, Liliana; Beltrán, A. M.; Günther, R.; Schmidt, Jennifer; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Porous Materials, 2018)
Keywords: Mesoporous particles; Scaffolds; Drug delivery; Silica; Silver

Morphology and topography of chitosan-Zn complex/PEO fiber mats influence cell viability and attachment - Mutlu, Nurshen; Kurtuldu, Fatih; Nowicka, Aleksandra; Liverani, Liliana; Galusek, Dušan; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2025)
Electrospun fiber mats with therapeutic potential show great promise as wound healing biomaterials. This study aims to compare the biophysical properties and biocompatibility of four different biodegradable fiber mats; namely chitosan and chitosan‑zinc complex (ChiZn)/(polyethylene oxide) PEO fibers, each with either nanometer-sized ( 200 nm) or micron-sized ( 1000 nm) diameters. Zn was incorporated to impact antibacterial properties of the fibers, ChiZn was synthesized using the in-situ precipitation method, and the influence of zinc chelation on the material structure and morphology was assessed using XRD, FTIR, XPS, and EDX, documenting the complexation and homogeneous distribution of zinc. ChiZn was then blended with PEO for electrospinning in a benign solvent system and crosslinked with glutaraldehyde vapor. SEM was used to examine fiber morphology while AFM documented a correlation between the roughness and fiber diameter. The effects of topography and composition on the viability, adhesion, and proliferation of stromal cells and mouse fibroblasts were investigated, showing higher cell viability on mats composed of nanosized fibers, whereas complex fiber mats composed of micron-sized fibers exhibited reduced cell viability. SEM evaluations showed that cells spread only on the surface of the nanosized fibers, independently of the presence of Zn, while cell infiltration into the mats was observed for micron-sized fibers.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Chitosan; Complexation; Electrospinning

Multifunctional zinc ion doped sol – gel derived mesoporous bioactive glass nanoparticles for biomedical applications - Neščáková, Zuzana; Zheng, Kai; Liverani, Liliana; Nawaz, Qaisar; Galusková, Dagmar; Kaňková, Hana; Michálek, Martin; Galusek, Dušan; Boccaccini, Aldo R. (Bioactive Materials, 2019)
Mesoporous bioactive glasses have been widely investigated for applications in bone tissue regeneration and, more recently, in soft tissue repair and wound healing. In this study we produced mesoporous bioactive glass nanoparticles (MBGNs) based on the SiO2–CaO system. With the intention of adding subsidiary biological function, MBGNs were doped with Zn2+ ions. Zn-MBGNs with 8 mol% ZnO content were synthesized via microemulsion assisted sol-gel method. The synthesized particles were homogeneous in shape and size. They exhibited spherical shape, good dispersity, and a size of 130 ± 10 nm. The addition of zinc precursors did not affect the morphology of particles, while their specific surface area increased in comparison to MBGNs. The presence of Zn2+ ions inhibited the formation of hydroxycarbonate apatite (HCAp) on the particles after immersion in simulated body fluid (SBF). No formation of HCAp crystals on the surface of Zn-MBGNs could be observed after 14 days of immersion. Interestingly, powders containing relatively high amount of zinc released Zn2+ ions in low concentration (0.6–1.2 mg L−1) but in a sustained manner. This releasing feature enables Zn-MBGNs to avoid potentially toxic levels of Zn2+ ions, indeed Zn-MBGNs were seen to improve the differentiation of osteoblast-like cells (MG-63). Additionally, Zn-MBGNs showed higher ability to adsorb proteins in comparison to MBGNs, which could indicate a favourable later attachment of cells. Due to their advantageous morphological and physiochemical properties, Zn-MBGNs show great potential as bioactive fillers or drug delivery systems in a variety of applications including bone regeneration and wound healing.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Bioactive glass; Bioactive particles; Bioactivity; Ion release; Sol-gel synthesis; Zinc

Multilayered scaffolds for interface tissue engineering applications - Liverani, Liliana; Boccaccini, Aldo R. (Electrofluidodynamic Technologies (EFDTs) for Biomaterials and Medical Devices, 2018)
Interface tissue engineering (ITE) deals with the fabrication of complex graded scaffolds for the regeneration of injured areas at the interface of different tissues. During the scaffold design process the focus is oriented to the replication of the native healthy tissues' complexity. This complexity could be achieved by introducing in the scaffolds gradients of morphology, composition' and function. In the present book chapter an overview of the multilayered scaffolds fabricated for ITE applications is reported. The versatility of the electrospinning technique for the development of gradient scaffolds and its suitability to be integrated with other scaffold fabrication techniques allowed the development of complex constructs with promising results in terms of cells' response. Examples of applications in the orthopedic field and for skin regeneration are also reported.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Electrospinning; Gradients; Interface tissue engineering; Multilayered scaffolds; Nanofibers

Multi-targeted B and Co co-doped 45S5 bioactive glasses with angiogenic potential for bone regeneration - Chen, Si; Michálek, Martin; Galusková, Dagmar; Michálková, Monika; Švančárek, Peter; Talimian, Ali; Kaňková, Hana; Kraxner, Jozef; Zheng, Kai; Liverani, Liliana; Galusek, Dušan; Boccaccini, Aldo R. (Materials Science and Engineering C, 2020)
Many elements, such as copper, cobalt (Co), strontium, magnesium and boron (B) have been used for single or multiple doping of bioactive glasses to promote angiogenesis during bone regeneration. However, few works have focused on promoting angiogenesis through stimulating several different signalling pathways which can be called a multi-target approach. In this study, 45S5 bioactive glass (BG) co-doped with B and Co was prepared by conventional melt quenching method. The synergistic effect of the two co-doping elements on angiogenesis promotion was expected. ATR-Fourier transform infrared spectroscopy, energy-dispersive X-ray spectroscopy and inductively coupled plasma-optical emission spectrometry were used to characterize the composition, element distribution and ion release of the samples, respectively. Results showed that the compositions of all samples were consistent with the design compositions and all elements were homogeneously distributed in the bulk glass. Different contents of B and Co led to different release rates of these elements. All samples showed bioactivity after immersion in simulated body fluid, regardless of the amount of doped B and Co. The 1% and 0.1% extracts of all samples did not show any cytotoxicity to MG-63 and ST-2 cells. Compared with single B or Co doping, the B and Co dual doped sample led to a stronger increase of the secretion of vascular endothelial growth factor from ST-2 cells, which supports and confirms the synergistic effect on angiogenesis of B and Co as co-doping elements in 45S5 BG.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Angiogenesis; Bioactive glass; Bone regeneration; Boron; Cobalt

Nanocomposite electrospun fibers of poly(ε-caprolactone)/bioactive glass with shape memory properties - Liverani, Liliana; Liguori, Anna; Zezza, Paola; Gualandi, Chiara; Toselli, Maurizio; Boccaccini, Aldo R.; Focarete, Maria Letizia (Bioactive Materials, 2022)
Electrospun fibers of shape memory triethoxysilane-terminated poly(epsilon-caprolactone) (PCL-TES) loaded with bioactive glasses (BG) are here presented. Unloaded PCL-TES, as well as PCL/BG nanocomposite fibers, are also considered for comparison. It is proposed that hydrolysis and condensation reactions take place between triethoxysilane groups of the polymer and the silanol groups at the BG particle surface, thus generating additional crosslinking points with respect to those present in the PCL-TES system. The as-spun PCL-TES/BG fibers display excellent shape memory properties, in terms of shape fixity and shape recovery ratios, without the need of a thermal crosslinking treatment. BG particles confer in vitro bioactivity to PCL-based nanocomposite fibers and favor the precipitation of hydroxycarbonate apatite on the fiber surface. Preliminary cytocompatibility tests demonstrate that the addition of BG particles to PCL-based polymer does not inhibit ST-2 cell viability. This novel approach of using bioactive glasses not only for their biological properties, but also for the enhancement of shape memory properties of PCL-based polymers, widens the versatility and suitability of the obtained composite fibers for a huge portfolio of biomedical applications.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Benign solvents; Bioactive glasses; Bioactivity; Electrospinning; PCL-TES; Shape memory polymers

Nanofiber composites in bone tissue engineering - Liverani, Liliana; Roether, Judith; Boccaccini, Aldo R. (Elsevier Inc., 2017)
Keywords: Bioactive glass; Bioactivity; Bone tissue engineering; Electrospinning; Hydroxyapatite; In vivo model; Nanocomposites; Nanofibers

Novel approach for the assessment of ovarian follicles infiltration in polymeric electrospun patterned scaffolds - Raffel, Nathalie; Dittrich, Ralf; Bäuerle, Tobias; Seyler, Lisa; Amir, Fattahi; Hoffmann, Inge; Leal-Egaña, Aldo; Beckmann, Matthias; Boccaccini, Aldo R.; Liverani, Liliana (PLoS ONE, 2019)
Reproductive tissue engineering (REPROTEN) has been recently defined as the application of the tissue engineering approach targeting reproductive organs and several research works are focusing on this novel strategy. Being still an innovative field, most of the scaffold characterization techniques suitable for other tissue targets give inappropriate results, and there is the need to evaluate and investigate novel approaches. In particular the focus of this paper is the evaluation of the infiltration of ovarian follicles inside patterned electrospun scaffolds. Beyond the standard techniques, for the first time the use of magnetic resonance imaging (MRI) for this purpose is proposed and specific protocols for scaffold preparation are reported. Positive results in terms of evaluation of scaffolds incorporating follicles confirm this technique as highly effective for further applications in this field.
CRIS-Team Scopus Importer:2019-05-17

Novel biomimetic fiber incorporated scaffolds for tissue engineering - Yongcong, Fang; Zhang, Ting; Liverani, Liliana; Boccaccini, Aldo R.; Sun, Wei (Journal of Biomedical Materials Research Part A, 2019)
From a structural perspective, an ideal scaffold ought to possess interconnected macro pores with sizes from 10 to 100 μm to facilitate cell infiltration and tissue formation, as well as similar topography to the natural extracellular matrix (ECM) which would have an impact on cell behavior such as cell adhesion and gene expression. For that purpose, here we developed a fabrication process to incorporate electrospun short fibers within freeze-dried scaffolds for tissue engineering applications. Briefly, PCL short fibers were first produced from electrospun fibers with ultrasonication method. They were then evenly dispersed in gelatin solution and freeze-dried to obtain fiber incorporated scaffolds. The resulting scaffolds exhibited hierarchical structure including major pores with sizes ranging from 50 to 150 μm and the short fibers dispersed in the thin walls of major pores, mimicking the fibrous feature of natural ECM. The short fibers were proven to modify the mechanical properties of scaffold and to facilitate cell adhesion and proliferation on the scaffold. As a promising scaffold for tissue engineering and regenerative medicine, the fiber incorporated scaffold may have further biomedical applications, in which the short fibers can act as drug release vehicles for growth factors or other biomolecules to promote vascularization.
CRIS-Team Scopus Importer:2019-08-27
Keywords: benign solvents; electrospinning; freeze drying; scaffold; tissue engineering

Numerical simulation of electrospinning process in commercial and in-house software PAK - Sustersic, Tijana; Liverani, Liliana; Boccaccini, Aldo R.; Savic, Slobodan; Janicijevic, Aco; Filipovic, Nenad (Materials Express, 2019)
Keywords: electrospinning; two-phase flow; electrospun fibers; numerical simulation

Optimization of cell seeding on electrospun PCL-silk fibroin scaffolds - Singh, Raminder; Eitler, David; Morelle, René; Friedrich, Ralf P.; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Liverani, Liliana; Cicha, Iwona (European Polymer Journal, 2020)
The availability of cell growth-supporting materials for regenerative medicine is limited. Here, we aimed to improve the attachment and growth of endothelial cells (HUVECs) and fibroblasts on electrospun poly(ε-caprolactone) (PCL) mats with different fiber diameters and on newly-established PCL and silk fibroin (PCL/SF) blended fibers obtained by using benign solvents (mixture of acetic acid and formic acid) for electrospinning. PCL mats were produced in two different average fiber diameters, namely micro and nano range. The electrospinning method was optimized to produce PCL/SF blended fibers. Morphology (F-actin), viability (calcein) and metabolic activity (WST-8 assay) of HUVECs and fibroblasts cultured in 2D on the mats of different fiber size and composition were compared. Subsequently, cylindrical PCL/SF scaffolds were produced and colonized with cells using 3D radial magnetic cell seeding. Both PCL and PCL/SF nanofibers provided better support for initial cell adhesion (day 1) compared with PCL microfibers. At day 7, the highest metabolic activity in HUVECs and fibroblasts was observed on PCL/SF mats. Microscopic studies confirmed that on day 7, the best support for cell growth was observed on PCL/SF. Tubular PCL/SF scaffolds were successfully colonized using magnetic nanoparticles and 3D radial magnetic cell seeding. Taken together, the fibers obtained by blending SF with PCL combine the mechanical benefits of PCL with improved biological functionality of SF. Electrospun PCL/SF nanofibers represent a promising material to produce both flat and 3D structures with potential for enhanced cell attachment and tissue regeneration.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Benign solvents; Electrospinning; Magnetic cell seeding; Nanofibers; Poly(ε-caprolactone); Silk fibroin

Optimization of Porcine Ovarian Follicle Isolation Methods for Better Developmental Potential - Fattahi, Amir; Liverani, Liliana; Dittrich, Ralf; Hoffmann, Inge; Boccaccini, Aldo R.; Beckmann, Matthias; Bleisinger, Nathalie (Tissue Engineering - Part A, 2020)
In the present study, we present a comparative analysis among the outputs of porcine follicle isolation using either mechanical technique alone or in combination with enzymes, proposing an optimized protocol useful for all further applications related to folliclein vitrogrowth and reproductive tissue engineering. The porcine follicles were isolated using mechanical technique alone (hand blender and scalpels) or in combination with collagenase or Liberase Dispase High (DH) at different doses applying different protocols. Finally, the number, morphology, and stage of isolated follicles were compared between the protocols. Moreover, the follicle viability (live/dead assay) and morphology (rhodamine phalloidin and 4 ',6-diamidino-2-phenylindole staining and scanning electron microscopy analysis) were evaluated after 10 days of culture. We found an optimum protocol for intact follicle isolation using the mechanical technique in combination with enzymes at a concentration of 0.5 mg/mL. However, the number of total isolated follicles and primordial follicles was significantly higher when collagenase was used compared to Liberase DH (p < 0.05), while Liberase DH could isolate a significantly higher percentage of preantral follicles. After 10 days of culture, the morphology and health status of follicles were statistically higher when Liberase DH was used in comparison with collagenase. Moreover, on the follicles extracted with Liberase DH, it was possible to observe theca cells covering part of the follicle surface. In conclusion, we demonstrated that the intact primary or secondary follicles could not be obtained using only mechanical methods, which led to the isolation of denuded oocytes and dramatically damaged follicles. We concluded that the collagenase-based follicle isolation could negatively affect the morphology and developmental potential of the follicles. Moreover, the incubation of ovarian cortex tissues with Liberase DH solution is an optimized protocol for porcine ovarian follicle isolation with developmental competence.
CRIS-Team WoS Importer:2020-07-24

Polycaprolactone Electrospun Fiber Mats Prepared Using Benign Solvents: Blending with Copper(II)-Chitosan Increases the Secretion of Vascular Endothelial Growth Factor in a Bone Marrow Stromal Cell Line - Gritsch, Lukas; Liverani, Liliana; Lovell, Christopher; Boccaccini, Aldo R. (Macromolecular Bioscience, 2020)
Inducing the formation of new blood vessels (angiogenesis) is an essential requirement for successful tissue engineering. Approaches have been proposed to enhance angiogenesis using growth factors and other biomolecules; however, this approaches present drawbacks in terms of high cost and patient safety. Copper is known to effectively regulate angiogenesis and can offer a more cost-effective alternative than the direct use of growth factors. With this study, a strategy to incorporate copper in electrospun fibrous scaffolds with pro-angiogenic properties is presented. Polycaprolactone (PCL) and copper(II)-chitosan are electrospun using benign solvents. The morphological and physicochemical properties of the fiber mats are investigated through scanning electron microscopy (SEM), static contact angle measurements, energy dispersive X-ray, and Fourier-transform infrared spectroscopies. Scaffold stability in phosphate buffered saline at 37 °C is monitored over 1 week. A bone marrow stromal cell line (ST-2) is cultured for 7 days and its behavior is evaluated using SEM, fluorescence microscopy and a tetrazolium salt-based colorimetric assay. Results confirm that PCL/copper(II)-chitosan is suitable for electrospinning. The fiber mats are biocompatible and favor cell colonization and infiltration. Most notably, the angiogenic potential of PCL/copper(II)-chitosan blends is confirmed by a three-fold increase in VEGF secretion by ST-2 cells in the presence of copper(II)-chitosan.
CRIS-Team Scopus Importer:2020-02-14
Keywords: angiogenesis; benign solvents; chitosan; copper; electrospinning; polycaprolactone

Polyglycerol hyperbranched polyesters: Synthesis, properties and pharmaceutical and biomedical applications - Zamboulis, Alexandra; Nakiou, Eirini A.; Christodoulou, Evi; Bikiaris, Dimitrios N.; Kontonasaki, Eleana; Liverani, Liliana; Boccaccini, Aldo R. (International Journal of Molecular Sciences, 2019)
In a century when environmental pollution is a major issue, polymers issued from bio-based monomers have gained important interest, as they are expected to be environment-friendly, and biocompatible, with non-toxic degradation products. In parallel, hyperbranched polymers have emerged as an easily accessible alternative to dendrimers with numerous potential applications. Glycerol (Gly) is a natural, low-cost, trifunctional monomer, with a production expected to grow significantly, and thus an excellent candidate for the synthesis of hyperbranched polyesters for pharmaceutical and biomedical applications. In the present article, we review the synthesis, properties, and applications of glycerol polyesters of aliphatic dicarboxylic acids (from succinic to sebacic acids) as well as the copolymers of glycerol or hyperbranched polyglycerol with poly(lactic acid) and poly(ε-caprolactone). Emphasis was given to summarize the synthetic procedures (monomer molar ratio, used catalysts, temperatures, etc.,) and their effect on the molecular weight, solubility, and thermal and mechanical properties of the prepared hyperbranched polymers. Their applications in pharmaceutical technology as drug carries and in biomedical applications focusing on regenerative medicine are highlighted.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Catalysts; Esterification reactions; Hyperbranched polymers; Medical and biomedical applications; Polycondensation; Polyglycerol polyesters

Poly(Glycerol Succinate) as Coating Material for 1393 Bioactive Glass Porous Scaffolds for Tissue Engineering Applications - Nakiou, Eirini A.; Lazaridou, Maria; Pouroutzidou, Georgia K.; Michopoulou, Anna; Tsamesidis, Ioannis; Liverani, Liliana; Arango Ospina, Marcela; Beketova, Anastasia; Boccaccini, Aldo R.; Kontonasaki, Eleana; Bikiaris, Dimitrios N. (Polymers, 2022)
Background: Aliphatic polyesters are widely used for biomedical, pharmaceutical and environmental applications due to their high biodegradability and cost-effective production. Recently, star and hyperbranched polyesters based on glycerol and ω-carboxy fatty diacids have gained considerable interest. Succinic acid and bio-based diacids similar to glycerol are regarded as safe materials according to the US Food and Drug Administration (FDA). Bioactive glass scaffolds utilized in bone tissue engineering are relatively brittle materials. However, their mechanical properties can be improved by using polymer coatings that can further control their degradation rate, tailor their biocompatibility and enhance their performance. The purpose of this study is to explore a new biopolyester poly(glycerol succinate) (PGSuc) reinforced with mesoporous bioactive nanoparticles (MSNs) as a novel coating material to produce hybrid scaffolds for bone tissue engineering. Methods: Bioactive glass scaffolds were coated with neat PGSuc, PGSuc loaded with dexamethasone sodium phosphate (DexSP) and PGSuc loaded with DexSP-laden MSNs. The physicochemical, mechanical and biological properties of the scaffolds were also evaluated. Results: Preliminary data are provided showing that polymer coatings with and without MSNs improved the physicochemical properties of the 1393 bioactive glass scaffolds and increased the ALP activity and alizarin red staining, suggesting osteogenic differentiation potential when cultured with adipose-derived mesenchymal stem cells. Conclusions: PGSuc with incorporated MSNs coated onto 1393 bioactive glass scaffolds could be promising candidates in bone tissue engineering applications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: 1393 bioactive glass scaffolds; bioactivity; dexamethasone; glycerol; mechanical properties; mesoporous nanoparticles; osteogenic differentiation; succinic acid

Poly(hydroxyalkanoate)s meet benign solvents for electrospinning - Brunetti, Lucia; Degli Esposti, Micaela; Morselli, Davide; Boccaccini, Aldo R.; Fabbri, Paola; Liverani, Liliana (Materials Letters, 2020)
Electrospinning (ES) technique allows the fabrication of nano/microfibers, relevant for tissue engineering (TE) applications. Several researches have been devoted to the use of benign solvents for ES, and in this work their use in combination with poly(hydroxyalkanoate)s (PHAs) is reported. Among PHAs, poly(3-hydroxybutyrate) (PHB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and their blend have been selected for their suitability for TE applications. The morphological and chemical properties of the electrospun mats, their degradation behaviour and cytocompatibility have been investigated, obtaining promising results and comparable properties with mats obtained using standard (not benign) solvents. Moreover, the fabrication of composite fibers incorporating bioactive glass (BG) particles is also reported as proof of concept.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Benign solvents; Bioactive glass; Electrospinning; Poly(hydroxyalkanoate)s; Tissue engineering

Polymer-derived Biosilicate-C composite foams: In-vitro bioactivity, biocompatibility and antibacterial activity - Dogrul, Fulden; Nawaz, Qaisar; Elsayed, Hamada; Liverani, Liliana; Galusek, Dušan; Bernardo, Enrico; Boccaccini, Aldo R. (Journal of the European Ceramic Society, 2024)
Biosilicate/carbon composites were fabricated in the form of highly porous foams by the polymer-derived ceramic route, and their biological response was analysed. Two different commercial silicone polymers (a poly-methyl-siloxane, MK, and a polymethyl-phenyl-silsesquioxane, H44) were considered as a silica source, mixed with active fillers yielding Na2O, CaO and P2O5. The samples were heat treated either in air or in N2 atmosphere to obtain products resembling the known Biosilicate® glass-ceramic, with or without free carbon. All fabricated samples exhibited acellular in-vitro bioactivity upon immersion in SBF as well as antibacterial activity against S. aureus and E. coli. Direct contact cell viability test, assessed by using a WST-8 assay, indicated that both carbon-containing and carbon-free samples were cytocompatible.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Antibacterial activity; biocompatibility; cell viability; Biosilicate glass-ceramic; Composites; Polymer-derived-ceramics; SiOC

Polymer-derived biosilicate®-like glass-ceramics: Engineering of formulations and additive manufacturing of three-dimensional scaffolds - Dogrul, Fulden; Ożóg, Paulina; Michálek, Martin; Elsayed, Hamada; Galusek, Dušan; Liverani, Liliana; Boccaccini, Aldo R.; Bernardo, Enrico (Materials, 2021)
Silicone resins, filled with phosphates and other oxide fillers, yield upon firing in air at 1100◦C, a product resembling Biosilicate® glass-ceramics, one of the most promising systems for tissue engineering applications. The process requires no preliminary synthesis of parent glass, and the polymer route enables the application of direct ink writing (DIW) of silicone-based mixtures, for the manufacturing of reticulated scaffolds at room temperature. The thermal treatment is later applied for the conversion into ceramic scaffolds. The present paper further elucidates the flexibility of the approach. Changes in the reference silicone and firing atmosphere (from air to nitrogen) were studied to obtain functional composite biomaterials featuring a carbon phase embedded in a Biosilicate®-like matrix. The microstructure was further modified either through a controlled gas release at a low temperature, or by the revision of the adopted additive manufacturing technology (from DIW to digital light processing).
CRIS-Team Scopus Importer:2021-09-24
Keywords: Additive manufacturing; Biosilicate® glass-ceramic; Digital light processing; Direct ink writing; Polymer-derived ceramics; SiOC

Polymer (PCL) fibers with Zn-doped mesoporous bioactive glass nanoparticles for tissue regeneration - Nescakova, Zuzana; Kankova, Hana; Galuskova, Dagmar; Galusek, Dusan; Boccaccini, Aldo R.; Liverani, Liliana (International Journal of Applied Glass Science, 2021)
Composite fibrous membranes based on poly(ɛ-caprolactone) (PCL) and mesoporous bioactive glass nanoparticles (MBGNs) were fabricated by electrospinning. MBGNs and Zn-doped MBGNs prepared by microemulsion sol–gel method were successfully incorporated inside the polymeric fibers of 240 and 385 nm in diameter for undoped and Zn-doped PCL_MBGNs fibers, respectively. Thermal analysis showed that the concentration of MBGNs reached a maximum of around 21 wt% for Zn-doped MBGNs. Both PCL_MBGNs and PCL_MBGNs_Zn composite membrane exhibited bioactivity after immersion in simulated body fluid (SBF). X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) showed the evolution of composite membranes, confirming the formation of hydroxyapatite (HAp). However, the degradation products of membranes did not affect the viability and proliferation of murine stromal cells (ST-2) and thus the new fiber structures represent a suitable environment for cell adhesion. Therefore, the incorporation of mesoporous glass nanoparticles doped with therapeutically active Zn2+ ions inside the PCL fibers offers the possibility to create a multifunctional biomaterial suitable for drug delivery and tissue engineering.
CRIS-Team Scopus Importer:2021-07-30
Keywords: benign solvents; composite fibers; composites; electrospinning; mesoporous bioactive glass nanoparticles; poly(ɛ-caprolactone); tissue engineering; zinc

Poly(ε-caprolactone)/bioactive glass composite electrospun fibers for tissue engineering applications - Piatti, Elisa; Miola, Marta; Liverani, Liliana; Verné, Enrica; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2023)
In this work, composite electrospun fibers containing innovative bioactive glass nanoparticles were produced and characterized. Poly(ε-caprolactone), benign solvents, and sol–gel B- and Cu-doped bioactive glass powders were used to fabricate fibrous scaffolds. The retention of bioactive glass nanoparticles in the polymer matrix, the electrospinnability of this novel solution and the obtained electrospun composites were extensively characterized. As a result, composite electrospun fibers characterized by biocompatibility, bioactivity, and exhibiting overall properties adequate for both hard and soft tissue engineering applications, have been produced. The addition of these bioactive glass nanoparticles was, indeed, able to impart bioactive properties to the fibers. Cell culture studies show promising results, demonstrating proliferation and growth of cells on the composite fibers. Wettability, degradation rate, and mechanical performance were also tested and are in line with previous results.
CRIS-Team Scopus Importer:2023-06-23
Keywords: benign solvents; bioactive glass; boron; composite; copper; electrospinning; poly(epsilon-caprolactone)

Poly(ε-caprolactone)/poly(glycerol sebacate) electrospun scaffolds for cardiac tissue engineering using benign solvents - Vogt, Lena; Ramos Rivera, Laura; Liverani, Liliana; Piegat, Agnieszka; El Fray, Miroslawa; Boccaccini, Aldo R. (Materials Science and Engineering C, 2019)
Electrospun fibers based on combinations of poly(ε-caprolactone) (PCL) and poly(glycerol sebacate) (PGS) have been studied for applications in cardiac tissue engineering. The aim of the present study is to demonstrate the fabrication of PCL and PGS prepolymer or mildly crosslinked PGS by electrospinning using less toxic solvents, like acetic acid, as opposed to conventional solvents such as chloroform or dichloromethane. The morphological and physiochemical properties and degradation susceptibility of the fiber mats were determined. A cell study using ST2 cells was performed to assess cytocompatibility. Neat PCL and PCL/PGS blends showed defect-free microstructures, whereby the average fiber diameter increased with the addition of PGS (0.8 ± 0.3 μm and 1.3 ± 0.7 μm, respectively). The mechanical properties were tested at 23 °C and 37 °C and showed higher values compared to native human myocardium. Degradation studies revealed a fast PGS degradation but the mildly cross-linked PGS resulted in acidification of the degradation medium. The biocompatibility was significantly increased when the samples were disinfected in 70% v/v ethanol in comparison to ultra-violet light disinfection. PCL/PGS fibers fabricated with acetic acid proved to be potentially suitable for application in cardiac tissue engineering based on their mechanical properties and biodegradability.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Acetic acid; Cardiac patch; Cardiac tissue engineering; Electrospinning; Poly(glycerol sebacate); Poly(ε-caprolactone)

Porous Biomaterials and Scaffolds for Tissue Engineering - Liverani, Liliana; Guarino, Vincenzo; La Carrubba, Vincenzo; Boccaccini, Aldo R. (Encyclopedia of Biomedical Engineering, 2019)
In the present article, an overview of the definition of tissue engineering and scaffold requirements is reported. In particular, scaffold porosity and its relevance for several tissue target regeneration is highlighted. Different scaffold fabrication techniques are reported and explained in details, highlighting advantages and disadvantages for all of these techniques, regarding the specific final applications.<br
CRIS-Team WoS Importer:2020-04-10
Keywords: Porosity; Scaffold fabrication techniques; Scaffolds; Tissue engineering

Positive effect of wrapping poly caprolactone/polyethylene glycol fibrous films on the mechanical properties of 45S5 bioactive glass scaffolds - Shi, Quan; Li, Zhi-Yong; Liverani, Liliana; Roether, Judith; Chen, Qiang; Boccaccini, Aldo R. (International Journal of Applied Ceramic Technology, 2018)
Keywords: electrospinning; mechanical properties; 45S5 bioactive glass scaffold; bone tissue engineering; poly caprolactone/polyethylene glycol film

Preparation and characterization of sintered bioactive borate glass tape - Sengupta, Susanta; Michalek, Martin; Liverani, Liliana; Švančárek, Peter; Boccaccini, Aldo R.; Galusek, Dušan (Materials Letters, 2021)
Non-aqueous tape casting was used to prepare flexible green tapes from borate glass (1393B3) particles. The tapes were sintered at 550, 575, 600 °C: dense tapes were prepared at 600 °C. In-vitro bioactivity in simulated body fluid (SBF) of tapes sintered at different temperatures was evaluated. SEM, FTIR and XRD results showed slow degradation of dense borate glass tape in SBF compared to the non-dense tapes sintered at different temperatures. Formation of HCA (hydroxy carbonated apatite) on sample surfaces was confirmed after 7D in SBF.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Bioactivity; Borate bioactive glass; Densification; Tape casting

Production of a novel poly(ɛ-caprolactone)-methylcellulose electrospun wound dressing by incorporating bioactive glass and Manuka honey - Schuhladen, Katharina; Vakamulla Raghu, Swathi Naidu; Liverani, Liliana; Neščáková, Zuzana; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2020)
Wound dressings produced by electrospinning exhibit a fibrous structure close to the one of the extracellular matrix of the skin. In this article, electrospinning was used to fabricate fiber mats based on the well-known biopolymers poly(ɛ-caprolactone) (PCL) and methylcellulose (MC) using benign solvents. The blend fiber mats were cross-linked using Manuka honey and additionally used as a biodegradable platform to deliver bioactive glass particles. It was hypothesized that a dual therapeutic effect can be achieved by combining Manuka honey and bioactive glass. Morphological and chemical examinations confirmed the successful production of submicrometric PCL-MC fiber mats containing Manuka honey and bioactive glass particles. The multifunctional fiber mats exhibited improved wettability and suitable mechanical properties (ultimate tensile strength of 3–5 MPa). By performing dissolution tests using simulated body fluid, the improved bioactivity of the fiber mats by the addition of bioactive glass was confirmed. Additionally, cell biology tests using human dermal fibroblasts and human keratinocytes-like HaCaT cells showed the potential of the fabricated composite fiber mats to be used as wound dressing, specially due to the ability to support wound closure influenced by the presence of bioactive glass. Moreover, based on the results of the antibacterial tests, it is apparent that an optimization of the electrospun fiber mats is required to develop suitable wound dressing for the treatment of infected wounds.
CRIS-Team Scopus Importer:2020-07-31
Keywords: bioactive glass; electrospinning; Manuka honey; methylcellulose; wound healing

Progress on Electrospun Composite Fibers Incorporating Bioactive Glass: An Overview - Ghorbani, Farnaz; Reiter, Theresa; Liverani, Liliana; Schubert, Dirk W.; Boccaccini, Aldo R.; Roether, Judith (Advanced Engineering Materials, 2023)
Electrospinning is a promising approach for the development of fibrous tissue engineering (TE) scaffolds suitable for hard and soft tissues. Apart from physicomechanical properties, electrospun fibers are required to incorporate bioactive cues to control cellular functions, including facilitating biomineralization and osteogenic differentiation in case of bone TE, as well as vascularization, to support successful tissue regeneration. In recent years, bioactive glass (BG) addition to electrospun biopolymer fibers has shown promising results in enhancing the properties of fibers, including the improvement of biological performance. In this article, a comprehensive overview of BG-containing electrospun polymer composite fibers is presented, identifying the parameters that affect the mechanical properties as well as the biological response in vivo and in vitro. Subsequently, the effects of BG addition on the properties of the scaffolds are discussed. Recent developments in the fields of bone regeneration, wound healing, and drug delivery using BG-containing electrospun fibrous scaffolds are described in detail. Essential aspects related to BG-polymer composite fibers for translational research in TE are highlighted for future research in this field.
CRIS-Team WoS Importer:2023-02-03

Scaffold-Mediated Immunoengineering as Innovative Strategy for Tendon Regeneration - Russo, Valentina; El Khatib, Mohammad; Prencipe, Giuseppe; Cervero-Varona, Adrian; Citeroni, Maria Rita; Mauro, Annunziata; Berardinelli, Paolo; Faydaver, Melisa; Haidar-Montes, Arlette A.; Turriani, Maura; Di Giacinto, Oriana; Raspa, Marcello; et al. (Cells, 2022)
Tendon injuries are at the frontier of innovative approaches to public health concerns and sectoral policy objectives. Indeed, these injuries remain difficult to manage due to tendon's poor healing ability ascribable to a hypo-cellularity and low vascularity, leading to the formation of a fibrotic tissue affecting its functionality. Tissue engineering represents a promising solution for the regeneration of damaged tendons with the aim to stimulate tissue regeneration or to produce functional implantable biomaterials. However, any technological advancement must take into consideration the role of the immune system in tissue regeneration and the potential of biomaterial scaffolds to control the immune signaling, creating a pro-regenerative environment. In this context, immunoengineering has emerged as a new discipline, developing innovative strategies for tendon injuries. It aims at designing scaffolds, in combination with engineered bioactive molecules and/or stem cells, able to modulate the interaction between the transplanted biomaterial-scaffold and the host tissue allowing a pro-regenerative immune response, therefore hindering fibrosis occurrence at the injury site and guiding tendon regeneration. Thus, this review is aimed at giving an overview on the role exerted from different tissue engineering actors in leading immunoregeneration by crosstalking with stem and immune cells to generate new paradigms in designing regenerative medicine approaches for tendon injuries.
CRIS-Team WoS Importer:2022-02-04

Simple fabrication technique for multilayered stratified composite scaffolds suitable for interface tissue engineering - Liverani, Liliana; Roether, Judith; Nooeaid, Patcharakamon; Trombetta, Marcella; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2012)
A straightforward method for manufacturing stratified scaffolds with potential application in osteochondral tissue engineering is reported. The method integrates three different techniques widely used for scaffold fabrication: sponge replica method, freeze-drying and electrospinning. 45S5 Bioglass® was used for the fabrication of the rigid bioactive substrate intended to be in contact with bone tissue, chitosan and alginate based solutions were used for building the interface between the Bioglass®-based scaffold and the soft cartilage side of the construct. Finally a chitosan-based electrospun nanofibrous membrane was selected for the upper layer of the scaffold. In this design, the intermediate layer has multiple functions providing adherence between the other scaffold components, preventing delamination and acting as a soft coating for the rigid Bioglass® substrate. Morphological analysis, bioactivity tests in simulated body fluid (SBF), as well as mechanical and wettability tests were performed on all samples to assess the optimal stratified scaffold combination. The best results, in terms of resistance to layer delamination, preservation of the bioactivity and improvement of the mechanical properties, were obtained using a chitosan solution and the freeze gelation technique for fabrication of the intermediate layer. Key results are discussed in the context of the potential application of these novel scaffolds in osteochondral tissue engineering.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.simple
Keywords: Composites; Tissue engineering; Scaffolds; Electrospinning; Chitosan; Bioactive glass

Sol–gel synthesis and characterization of ysz nanofillers for dental cements at different temperatures - Beketova, Anastasia; Theocharidou, Anna; Tsamesidis, Ioannis; Rigos, Athanasios E.; Pouroutzidou, Georgia K.; Tzanakakis, Emmanouil George C.; Kourtidou, Dimitra; Liverani, Liliana; Arango Ospina, Marcela; Anastasiou, Antonios; Tzoutzas, Ioannis G.; Kontonasaki, Eleana (Dentistry Journal, 2021)
Background: Yttria-stabilized zirconia nanoparticles can be applied as fillers to improve the mechanical and antibacterial properties of luting cement. The aim of this study was to synthesize yttria-stabilized zirconia nanoparticles by the sol–gel method and to investigate their composition, structure, morphology and biological properties. Methods: Nanopowders of ZrO2 7 wt% Y2O3 (nY-ZrO) were synthesized by the sol–gel method and were sintered at three different tempera-tures: 800, 1000 and 1200◦C, and their composition, size and morphology were investigated. The biocompatibility was investigated with human gingival fibroblasts (hGFs), while reactive oxygen species (ROS) production was evaluated through fluorescence analysis. Results: All synthesized materials were composed of tetragonal zirconia, while nanopowders sintered at 800◦C and 1000◦C additionally contained 5 and 20 wt% of the cubic phase. By increasing the calcination temperature, the crystalline size of the nanoparticles increased from 12.1 nm for nY-ZrO800 to 47.2 nm for nY-ZrO1200. Nano-sized particles with good dispersion and low agglomeration were received. Cell culture studies with human gingival fibroblasts verified the nanopowders’ biocompatibility and their ROS scavenging activity. Conclusions: the obtained sol–gel derived nanopowders showed suitable properties to be potentially used as nanofillers for dental luting cement.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Chemical precipitation; Gingival fibroblasts; Nanoparticle; Oxidative stress; Toxicity tests; Yttrium; Zirconium

Soy protein meets bioactive glass: Electrospun composite fibers for tissue engineering applications - Tansaz, Samira; Liverani, Liliana; Vester, Lars; Boccaccini, Aldo R. (Materials Letters, 2017)
Soy protein isolate (SPI) was used to produce electrospun nanofibers, intended for tissue engineering (TE) applications. For the first time electrospun composite fibers have been successfully fabricated by the addition of nano and micron-sized 45S5 bioactive glass (BG) powders to SPI solution. The influence of BG particles on electrospun fiber morphology and mechanical properties was investigated. Optimization of electrospun parameters with focus on environmental factors indicated the need to control humidity for SPI fibers fabrication.
Keywords: Soy protein isolate Electrospinning Bioactive glass Nanofibers Tissue engineering

Synthesis and characterization of silver-doped mesoporous bioactive glass and its applications in conjunction with electrospinning - Ciraldo, Francesca; Liverani, Liliana; Gritsch, Lukas; Goldmann, Wolfgang; Boccaccini, Aldo R. (Materials, 2018)
Keywords: Bioactive glass; Antimicrobial; Ordered mesoporous glass; Electrospinning; Silver; Scaffolds

Synthesis of monodispersed Ag-doped bioactive glass nanoparticles via surface modification - Kozon, Dominika; Zheng, Kai; Boccardi, Elena; Liu, Yufang; Liverani, Liliana; Boccaccini, Aldo R. (Materials, 2016)
Keywords: Antibacterial activity; Bioactive glass nanoparticle; Bioactivity; Silver; Surface modification

THREE-DEMENSIONAL (3D) BIONTLAIETIC CULTURE ON POLY(EPSILON CAPROLACIONE) (PCL) PATTERNED SCAFFOLDS: A TISSIT ENGINEERING APPROACH TARGETING EARLY STAGE OF FOLLI-CULOGENESIS UP TO OOCYTE MATURATION - Di Berardino, Chiara; Peserico, Alessia; Liverani, Liliana; Capacchietti, Giulia; Russo, Valentina; Bernabo, Nicola; Boccaccini, Aldo R.; Barboni, Barbara (FERTILITY AND STERILITY, 2022)
CRIS-Team WoS Importer:2023-03-17

Tissue Engineering Using Ceramics and Polymers, Third Edition - Boccaccini, Aldo R.; Ma, Peter X.; Liverani, Liliana (Elsevier, 2021)
Tissue Engineering Using Ceramics and Polymers, Third Edition is a valuable reference tool for both academic researchers and scientists involved in biomaterials or tissue engineering, including the areas of bone and soft-tissue reconstruction, repair and organ regeneration. With its distinguished editors and international team of contributors, this book reviews the latest research and advances in this thriving area and how they can be used to develop treatments for disease states. New sections cover nanobiomaterials, drug delivery, advanced imaging and MRI for tissue engineering, and characterization of vascularized scaffolds. Technology and research in the field of tissue engineering has drastically increased within the last few years to the extent that almost every tissue and organ of the human body could potentially be regenerated with the aid of biomaterials. .
CRIS-Team Scopus Importer:2024-12-16

Versatile bioactive and antibacterial coating system based on silica, gentamicin, and chitosan: Improving early stage performance of titanium implants - Ballarre, Josefina; Aydemir, T.; Liverani, Liliana; Roether, Judith; Goldmann, Wolfgang; Boccaccini, Aldo R. (Surface & Coatings Technology, 2019)
The aim of this work is to develop and characterize a multifunctional and dual surface coating system for titanium orthopedic implants by applying two different cost-effective, scalable, and non-complex coating technologies (spray and electrophoretic deposition). The first deposit is formed by a sprayed hybrid sol-gel layer combined with bioactive glass particles (45S5, BG), and the outer part of the dual coating consists of a chitosan-gelatin/silica (Si) - antibiotic (gentamicin, Ge) composite layer applied by electrophoretic deposition. The application of sol-gel enclosed BG drops onto the surface was done to enhance the bioactivity of the double-layered surface coating system. After the BG is dissolved, thus generating a calcium‑silicon rich medium, the re-deposition of hydroxyl‑carbonate apatite occurs. Regarding the antibacterial inhibition properties, antibacterial activity to both strains used (S. aureus and E. coli) was obtained for the chitosan/gelatin/Si[sbnd]Ge nanoparticle coatings on titanium substrates, showing a large inhibition area around the samples. Both the bare Ti samples and the coatings with chitosan/gelatin matrix did not successfully inhibit bacterial growth. As expected, the presence of silica-based glasses and coatings based on amorphous silica enhanced cell viability. The deposition of BG was done with the aim of extending the bioactive effect of the system, considering the presence of a porous degradable organic layer deposited on top, which was shown to be partially degraded after 7 days. The sol gel sprayed BG layer combined with chitosan/gelatin biopolymers filled with Si[sbnd]Ge nanoparticles presents a suitable technology to generate bioactive and antibacterial surfaces to enhance Ti implant performance.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Antibacterial effect; Bioactive glass; Bioactivity; Electrophoretic deposition; Silica-gentamicin nanoparticles; Titanium

Versatile production of poly(Epsilon-caprolactone) fibers by electrospinning using benign solvents - Liverani, Liliana; Boccaccini, Aldo R. (Nanomaterials, 2016)
Keywords: Benign solvents; Bioactive glass; Composite; Electrospinning; Macroporosity; Nanofibers; Poly(epsilon-caprolactone)

When Electrospun Fiber Support Matters: In Vitro Ovine Long-Term Folliculogenesis on Poly (Epsilon Caprolactone) (PCL)-Patterned Fibers - Di Berardino, Chiara; Liverani, Liliana; Peserico, Alessia; Capacchietti, Giulia; Russo, Valentina; Bernabo, Nicola; Tosi, Umberto; Boccaccini, Aldo R.; Barboni, Barbara (Cells, 2022)
Current assisted reproduction technologies (ART) are insufficient to cover the slice of the population needing to restore fertility, as well as to amplify the reproductive performance of domestic animals or endangered species. The design of dedicated reproductive scaffolds has opened the possibility to better recapitulate the reproductive 3D ovarian environment, thus potentially innovating in vitro folliculogenesis (ivF) techniques. To this aim, the present research has been designed to compare ovine preantral follicles in vitro culture on poly(epsilon-caprolactone) (PCL)-based electrospun scaffolds designed with different topology (Random vs. Patterned fibers) with a previously validated system. The ivF performances were assessed after 14 days under 3D-oil, Two-Step (7 days in 3D-oil and on scaffold), or One-Step PCL protocols (14 days on PCL-scaffold) by assessing morphological and functional outcomes. The results show that Two- and One-Step PCL ivF protocols, when performed on patterned scaffolds, were both able to support follicle growth, antrum formation, and the upregulation of follicle marker genes leading to a greater oocyte meiotic competence than in the 3D-oil system. In conclusion, the One-Step approach could be proposed as a practical and valid strategy to support a synergic follicle-oocyte in vitro development, providing an innovative tool to enhance the availability of matured gametes on an individual basis for ART purposes.
CRIS-Team WoS Importer:2022-07-08

Zinc improves antibacterial, anti-inflammatory and cell motility activity of chitosan for wound healing applications - Mutlu, Nurshen; Liverani, Liliana; Kurtuldu, Fatih; Galusek, Dušan; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2022)
We report the successful preparation and characterization of chitosan-Zn complex (ChiZn) in the form of films, intended to enhance the biological performance of chitosan by the presence of Zn as antibacterial agent and biologically active ion. The influence of Zn chelation on morphology and structure of chitosan was assessed by scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy and infrared spectroscopy. The biodegradability study of ChiZn showed a sustained release of Zn up to 2 mg/mL. No toxic response was observed toward stromal cell line ST-2 in indirect contact with the ChiZn films. The dissolution product of ChiZn showed improved wound closure (88% closure) compared to the positive control group (70% closure). Moreover, ChiZn exhibited antibacterial activity against S. aureus together with a slight increase ( 30%) in the secretion of VEGF and moderate decrease in nitric oxide evolution. Our findings indicate that ChiZn could be used as a safe and effective wound healing agent.<br
Keywords: Chitosan‑zinc complex; Chelation process; Wound healing; Antibacterial activity